IMPLEMENTATION OF SHARIA BANKS - Nofinawati, Nofinawati (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Palangka Raya, 2018)
Social function of Sharia Banks is to receive funds i.e. zakat, infaq, sedekah, wakaf, hibah, and distribute them in accordance to sharia laws under the banks